2020
DOI: 10.1109/access.2020.2999160
|View full text |Cite
|
Sign up to set email alerts
|

Direct Answers in Google Search Results

Abstract: This study aims to explore Google's new "featured snippet" (a direct answer that appears in web search results) to better understand the method of extracting and displaying such answers above regular ranked results. The motivation for the study was to investigate form, structure, and relation to query, content, and domain of the direct answer. This study utilized a dataset of 743,798 keywords and the displayed direct answers. It also included web search data for every direct answer, e.g. resulting domain, full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
(60 reference statements)
0
7
0
2
Order By: Relevance
“…Una respuesta destacada o featured answer es un fragmento o resumen extraído del texto de una página web que responden de forma directa a una consulta ejecutada en el buscador (Miklosik, 2019;Strzelecki & Rutecka, 2020a). Los fragmentos destacados tratan de proporcionar una respuesta completa ya sea simple o con varios pasos o piezas de información (por ejemplo, respuestas a how to?).…”
Section: Featured Answerunclassified
See 1 more Smart Citation
“…Una respuesta destacada o featured answer es un fragmento o resumen extraído del texto de una página web que responden de forma directa a una consulta ejecutada en el buscador (Miklosik, 2019;Strzelecki & Rutecka, 2020a). Los fragmentos destacados tratan de proporcionar una respuesta completa ya sea simple o con varios pasos o piezas de información (por ejemplo, respuestas a how to?).…”
Section: Featured Answerunclassified
“…Respecto al buscador, la percepción del usuario mejora con los resultados directos pues el acceso directo permite descartar cualquier otro resultado orgánico. Desde el punto de vista del recurso, las páginas web experimentan una mayor visibilidad y un aumento del tráfico (Strzelecki & Rutecka, 2020a;Duong, 2019), contribuyendo a mejorar su autoridad del dominio. Desde el punto de vista del usuario, algunos trabajos han estudiado cómo las respuestas enriquecidas condicionan a los internautas quienes tienden a sobrevalorar la confianza en un sitio web (Bernstein et al, 2012;Lurie & Mustafaraj, 2018).…”
Section: Selección De Rich Answersunclassified
“…Over time, Google–emulated to some extent by other, less popular search engines–has introduced several types of answer boxes, among them: a rich answer box (a type of featured snippet that includes additional information such as a graph, table, image, or interactive tool), a news stories box, a knowledge box (often information from Wikipedia displayed in the upper-right-hand corner of the search results page), a box suggesting related searches, and so on [ 64 , 65 ]. Our focus, however, is on what Google calls the “featured snippet,” a relatively small box that is unlabeled and contains a simple answer to a user’s query [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study published in 2017, 12.3% of the 112 million search queries examined produced featured snippets, and the appearance of snippets reduced user clicks to the first search result from 26.0% to 19.6% [ 118 ]. A more recent study found that shorter phrases in a search bar are more likely to generate featured snippets [ 65 ], and featured snippet sources have been found to vary by location [ 119 ]. A 2019 study found significant liberal bias in Google’s news boxes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we now have "Featured snippets" available on these major search engines. To date, 15% of results answering questions such as who -what -how -where contain featured snippets [25], [26].…”
Section: Introductionmentioning
confidence: 99%